Morbidity and maternal and infant outcomes of hypertensive disorder in pregnancy in China in 2018. Issue 6 (31st March 2021) - Lyu, Xin; Zhang, Weiyuan; Zhang, Jingxiao; Wei, Yuqian; Guo, Xiaoli; Cui, Shihong; Yan, Jianying; Zhang, Xiaoyan; Qiao, Chong; Zhou, Rong; Gu, Weirong; Chen, Xianxia; et al.
Abstract: Hypertensive disorder in pregnancy is a disease that occurs during pregnancy. We aimed to analyze the morbidity and maternal and infant outcomes with respect to the hypertensive disorder in pregnancy in China in 2018. Clinical data of 38 590 cases from 161 hospitals were retrospectively collected. The differences in morbidity and maternal and infant mortality among the major regions and provinces were compared. The overall national average morbidity was 4.74%, and the ratios of gestational hypertension, preeclampsia, eclampsia, chronic hypertension, and chronic hypertension with superimposed preeclampsia were 29.17%, 55.02%, 0.66%, 6.53%, and 8.62%, respectively. The overall maternal mortality was 0.61/100 000, and the case fatality was 0.13%. Morbidity associated with hypertensive disorder in pregnancy was 7.74% in North China, 6.62% in Northwest China, 6.40% in Central China, 5.83% in Northeast China, 4.28% in East China, 3.85% in South China, and 2.88% in Southwest China. The morbidity in each province was 1.62‐11.28%. The overall perinatal mortality was 3.59% (81.09% for stillbirths; 18.91% for neonatal deaths). Perinatal mortality decreased with increasing gestational weeks from 24 to 37 + 6 weeks. Perinatal mortality for delivery at 32 weeks of gestation in all regions of the country was <10%. Morbidity varied across regions in China, with the lowest in Southwest and the highest in North China. The low maternal mortality is related to the large‐scale development of standardized maternal health care in China. For severe hypertensive disorder patients, gestation should be prolonged to 32 weeks as often as possible for better neonatal survival rates.